Perancangan Jaringan LTE-Advanced Dengan Metode Carrier Aggregation (CA) Intra-Band Contiguous Di Kota Pekanbaru - Ridho Yatullah; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The rapid technological developments in the telecommunications world increase the need for reliable data access in order to exchange information can be faster and more stable. To resolve this, a mobile broadband technology was developed called LTE Release 10 or LTE-Advanced (LTE-A). LTE-Advanced is a 3GPP release 10 technology where bandwidth usage maximized through Carrier Aggregation (CA). In this study, the design of the LTE-Advanced network in Pekanbaru City with the Carrier Aggregation Intra-Band Contiguous Method uses 1800 MHz frequency band with 5 MHz and 20 MHz bandwidth. The design was carried out based on capacity and coverage planning and then simulated with Atoll Software. The parameters analyzed in the simulation are Signal Level, User Connected and Throughput and then be compared with planning without carrier aggregation.Keywords : Carrier Aggregation, LTE-Advanced, Signal Level, Throughput, User Connected